The impact of organised educational campaigns on understanding of needle sticks injuries and related post-exposure HIV/AIDS prophylaxis - Ram Kumar Garg; Pooja Koundal; Poonam Sharma; Yogesh Kumar; Ram Niwas; Jitendra Singh (Journal of Family Medicine and Primary Care)
Background: For those who often use needles, such as nurses and laboratory professionals, needle stick injuries are a fact of life. Even if it’s not medical waste, it can still happen if you touch garbage. Approximately 385,000 healthcare professionals stab themselves unintentionally each year. The likelihood of virus transmission after a skin puncture injury depends on the person who used the object in the first place, the quantity of blood involved, the type of needle or syringe in question, the length of time since it was last used, and the type of injury. Post-exposure prophylaxis should be taken into account. Objective: The objective of the study is to assess the impact of a structured educational campaign on nursing students’ understanding of needle stick injuries and related post-exposure prophylaxis for HIV/AIDS. Methodology: Quasi experimental research design was used. Sixty nursing students B.Sc (N) and GNM (N) 1st year students were selected by using purposive sampling technique. The study was conducted at selected private nursing colleges at District Kangra, Himachal Pradesh. Results: In the pre-test knowledge score, (25%) nursing students had poor level of knowledge, (66.66%) nursing students had average level of knowledge, and (8.34%) nursing students had good level of knowledge. The post-test knowledge score (43.34%) nursing students had good level of knowledge, (56.66%) nursing students had average level of knowledge, and (0%) nursing students had poor level of knowledge The t value in the group was 9.50 which were highly significant at P < 0.05 level. Conclusion: Compared to video-assisted instruction, the lecture and demonstration technique is more successful. The fact that both teaching techniques contribute to improving understanding of HIV/AIDS and needle stick injuries.